2014
DOI: 10.1371/journal.pone.0098368
|View full text |Cite
|
Sign up to set email alerts
|

A Pro-Atherogenic HDL Profile in Coronary Heart Disease Patients: An iTRAQ Labelling-Based Proteomic Approach

Abstract: ObjectivesThis study aims to compare the protein composition of high-density lipoprotein (HDL) particles in coronary heart disease (CHD) patients and controls by proteomic methods.BackgroundHDL has been reported to exert pro-atherogenic properties in CHD patients. Accumulating evidence indicates that HDL composition, rather than the HDL-C level, determines its functions. The changes in HDL composition involved in the conversion of anti-atherogenic to pro-atherogenic properties in CHD patients are currently unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 61 publications
1
35
0
Order By: Relevance
“…A plethora of recent papers has documented changes in the HDL proteome in disorders ranging from CVD and rheumatoid arthritis to diabetes and metabolic syndrome [7481]. Many of these studies have centered on mechanistic implications of the observed changes in the HDL proteome.…”
Section: Translational Studies: Hdl In Renal Disease Subjectsmentioning
confidence: 99%
“…A plethora of recent papers has documented changes in the HDL proteome in disorders ranging from CVD and rheumatoid arthritis to diabetes and metabolic syndrome [7481]. Many of these studies have centered on mechanistic implications of the observed changes in the HDL proteome.…”
Section: Translational Studies: Hdl In Renal Disease Subjectsmentioning
confidence: 99%
“…1518 Importantly, several plasma protein biomarkers of NAFLD and CVD have been identified. 1921 Although the static measurements of protein abundance are important, they do not allow an understanding of the mechanism for these changes.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, HDL isolated from CVD patient plasma identifi ed 196 proteins associated with HDL particles, of which four showed increased expression in CVD patients, whereas a further seven proteins were decreased compared with normal controls ( 38 ). Using MS, and with verifi cation by ELISA, SAA showed a highly signifi cant increase in patient samples, whereas apoC-I levels showed a signifi cant decrease compared with controls.…”
mentioning
confidence: 98%